PENILE TORSION OF A TWO-YEAR-OLD BOY: A CASE REPORT - Putra, Fikri Alam Riza; Daryanto, Besut; Nurhadi, Pradana (Indonesian Journal of Urology, 2024)
Objective: This case report presented Penile Torsion in pediatrics. Case(s) Presentation: A two-year-old boy with a chief complaint of rotated penile to the right side since birth. There were 45º in clockwise torsion, slight chordee, and uncircumcised. Patient underwent penile reconstruction surgery, including penile degloving, urethral mobilization, and plication. After seven days follow-up, parents were satisfied with straight penile erection and no torsion at all. After 3 months follow-up, parents reported satisfaction with the surgical outcome such as cosmetic appearance, straight erection, and normal stream urine. Discussion: Surgical techniques ranging from simple penile degloving with foreskin repositioning to more complex surgical procedure involving corporeal tissue. Surgery by using degloving of penile skin and realignment could be suitable for penile torsion <90°. For the cases of >90°, other techniques should be considered such as corporopexy procedure, rotation flap of dorsal dartos, or diagonal suturing of corporeal folds away from and parallel to the neurovascular bundle. Conclusion: Penile reconstruction surgery using penile degloving, urethral mobilization, and plication for penile torsion showed satisfaction result including cosmetic appearance, penile erection, and normal urine flow. Keywords: Chordee, penile reconstruction, penile torsion.